PENGEMBANGAN MODEL PEMBELAJARAN FISIKA SMK MELALUI KEGIATAN BENGKEL OTOMOTIF UNTUK MENUMBUHKAN SOFT SKILLS SISWA - Hartini, Puji (JPP, 2011)
The background study of this research is to develop a learning model of the world oftemperature and heat for vocational school that does not have a physics laboratorium andalso to improve SMK students soft skills who want to enter the world of work. The goalsof this research are (1) developing a learning model to study temperature and heatthrough automotive workshop activity (2) knowing the learning model contribution oftemperature and heat through automotive workshop activity on improving vocationalstudentsÃ¢â¬â¢ soft skills. This research material is temperature and heat, and the subject ofthis research is the 1Ith grade students of SMK 1 Sukoharjo, Wonosobo which consist ofthree classes. One class acts as small-scale experiment group, and two classes act aslarge-scale experiment group. The method used in this research is the Research and Developmentmethod (R&D). Data where gathered from self-evaluation list about soft skillsthrough pre-test and post-test and observation. Implementation data of this learningmodel were taken from the score level of learning accomplishment. The analysis of softskills being used in this research is the score taken into percentage, whereas normality,homogencity and differential test are using SPSS. Analysis results of the students softskills percentage in the first small-scale experiment is 31%, in the second small-scale experimentis 44%, in the third small scale experiment is 59%, and differential test forthose three experiments show significant difference, which means there is an improvementof soft skills on each experiment. The results of the percentage analysis for largescaleexperiments on experimental class for the improvement of studentsÃ¢â¬â¢ soft skillsthrough pre-test and post-test score is 65% whereas control class is 38%. SPSS analysisof the data are normally distributed and homogenous, differential test shows that the experimentalclass gives a better result than control class, so it can be concluded that thelearning model through automotive workshop activity is effectively improving vocationalscholl studentsÃ¢â¬â¢ soft skills.Keywords: Soft Skills, Learning Model, Vocational Automotive.